KULTUREL VIDENSDIVERSITET: Om videnssystemers lukkede ontisk-epistemiske fantasier og nødvendigheden af vidensmægling - Hasse, Cathrine (Tidsskriftet Antropologi, 2006)
Cultural diversity is often taken to be something visible. We perceive others as different from us on the basis of their different colours of skin, signs of gender, age, their clothes etc. In this article I argue that we should be more attentive towards the invisible diversity. This includes an increased focus on the processes behind our perception of cultural diversity in the visible world. I argue that cultural learning processes are what can be recognized as cultural differences. Learning involves an incorporated knowledge of practice. When this normally tacit body knowledge is called forth in confrontations, brokers are needed who can understand better the often misunderstood words spoken in conflicts. The incorporated knowledge makes words meaningful for some, who share the learning in practice the words refer to, and unintelligible for others, who do not. Such brokers are important in open conflict, but they are perhaps most important when we naively accept communicated messages from influential people. We need brokers who know how to translate the practice of everyday body knowledge in cultural worlds – even when we from visible surfaces consider us as part of the same culture. We need brokers who can open up complexities, where none were seen and who can make us understand that even apparently innocent words and appearances can be understood in deeper ways demanding a new form of incorporated knowledge. In the “world of physics”, I argue, such brokers are necessary for a more democratic world. The most likely brokers are anthropologists, who do not settle for surfaces, but insist on reflecting on their own incorporated cultural learning processes.